Efecto de la fertilización de las variedades de café ecorobusta, napopayamino y conilón (coffea canephora) en la etapa de producción - Barre Alava, Francisca Alexandra (2022)
The research project was carried out at the "Sacha wiwa" Experimental Center, Guasaganda parish, and lasted 98 days, with the following objectives: The nutritional requirements of the Ecorobusta, Napopayamino and Conilón coffee varieties in the study area were determined; the agronomic response of the Ecorobusta, Napopayamino and Conilón coffee varieties to the application of fertilization was determined; and the production costs of the Ecorobusta, Napopayamino and Conilón coffee varieties in the production stage were established. Four treatments with four fertilization programs were used. The results show that the nutritional requirements of the Ecorobusta, Napopayamino and Conilón coffee varieties in the study area were determined by laboratory analysis, highlighting that the pH of the soil of the evaluated treatments was moderately acid in Ecorobusta and Conilón and required lime in Napopayamino; the organic matter presented average values; N, P and K were low, requiring the application of nutritional mixtures. The agronomic response of the coffee varieties to the application of fertilization, the formula 1000 kg ha FI + FO obtained the highest values in plant height (182 cm) and stem diameter (4.29 cm), while the highest number of branches (23.35 branches on average) with the dose of fertilizer 1500 kg ha FI + FO. The yield in the variety Conilon with 350.78 kg ha. The production costs of the coffee varieties Ecorobusta, Napopayamino and Conilón in the production stage with nutritional mixtures are similar (30.19, 30.11 and 30.53 USD), differing widely from the control treatment which resulted in a lower value.